HAWK and HARRIER: Ninety-Six-Week Outcomes from the Phase 3 Trials of Brolucizumab for Neovascular Age-Related Macular Degeneration - Dugel, Pravin U; Singh, Rishi P; Koh, Adrian; Ogura, Yuichiro; Weissgerber, Georges; Gedif, Kinfemichael; Jaffe, Glenn J; Tadayoni, Ramin; Schmidt-Erfurth, Ursula; Holz, Frank G (Ophthalmology (Rochester, Minn.), 2021)
To report the 96-week outcomes from HAWK and HARRIER. Phase 3, prospective, randomized, double-masked, multicenter studies comparing efficacy and safety of brolucizumab 3 mg (HAWK only) and 6 mg with aflibercept 2 mg in eyes with neovascular age-related macular degeneration (nAMD). Treatment-naïve eyes with nAMD were randomized 1:1:1 to brolucizumab 3 mg (n = 358), brolucizumab 6 mg (n = 360), aflibercept 2 mg (n = 360; HAWK) or 1:1 to brolucizumab 6 mg (n = 370), aflibercept 2 mg (n = 369; HARRIER). After 3 monthly loading doses, brolucizumab patients received every (q)-12-week (w) dosing, possibly adjusting to q8w dosing if disease activity was present at predefined disease activity assessment (DAA) visits. Aflibercept was dosed in a fixed q8w regimen. Visual and anatomic parameters were assessed throughout. Primary end point was at week 48 (48w), confirmed at 96w. Mean best-corrected visual acuity (BCVA) change from baseline, proportion of patients on an q12w regimen, retinal thickness, retinal fluid changes, and safety, all to 96w. Mean change (least squares [LS] mean ± standard error) in BCVA from baseline to 96w in HAWK was 5.6±0.79 Early Treatment Diabetic Retinopathy Study (ETDRS) letters for brolucizumab 3 mg, 5.90±0.78 letters for brolucizumab 6 mg, and 5.3±0.78 letters for aflibercept and in HARRIER was 6.1±0.73 letters for brolucizumab 6 mg and 6.6 ± 0.73 letters for aflibercept. Greater central subfield thickness reductions were observed with brolucizumab 6 mg versus aflibercept in HAWK (LS mean, -174.8 μm vs. -148.7 μm; 95% confidence interval for treatment difference, -46.2 to -5.9 μm; P = 0.0115) and HARRIER (LS mean, -197.7 μm vs. -155.1 μm; 95% confidence interval for treatment difference, -62.0 to -23.3 μm; P < 0.0001). The proportions of eyes with intraretinal fluid and/or subretinal fluid (IRF/SRF) at 96w in HAWK were 31% (P = 0.0688) and 24% (P = 0.0002) for brolucizumab 3 mg and 6 mg and 37% for aflibercept, whereas in HARRIER, they were 24% for brolucizumab 6 mg (P < 0.0001) and 39% for aflibercept. At 92w (last DAA), a 45.4% and 38.6% probability was observed for brolucizumab 6 mg patients of maintaining an q12w treatment regimen in HAWK and HARRIER, respectively. Brolucizumab exhibited an overall well-tolerated safety profile. Visual outcomes from 48w to 96w confirm the efficacy achieved at 48w. Brolucizumab demonstrated greater fluid resolution compared with aflibercept. The q12w potential for brolucizumab observed at 48w was maintained to 96w.